Dysbiosis and genomic plasticity in the oily scalp microbiome: a multi-omics analysis of dandruff pathogenesis - Yu, Han; Li, Jiayi; Wang, Yan; Zhang, Tongze; Mehmood, Tahir; Habimana, Olivier (Frontiers in Microbiology, 2025)
IntroductionDandruff, affecting ~50% of the global population, is a prevalent scalp condition linked to microbial dysbiosis and inflammation, significantly impacting quality of life.MethodsThis study employed an integrative omics approach, utilizing 16S rRNA and ITS1 amplicon sequencing alongside shotgun metagenomics, to analyze the scalp microbiome of 65 individuals with varying scalp conditions (healthy oily, healthy non-oily, and dandruff oily).ResultsDistinct microbial profiles were identified, with an increased abundance of pathogenic genera such as Staphylococcus in the dandruff oily (DO) group, contrasted with the presence of Cutibacterium in healthy cohorts.DiscussionFunctional profiling revealed elevated DNA repair mechanisms in the DO group, indicative of stress stemming from pathogen overgrowth, while healthy non-oily samples demonstrated enhanced functions for scalp homeostasis. Notably, the increase in genomic plasticity in the DO group, characterized by antimicrobial resistance genes and mobile elements, underscores the complex interplay of microbial dynamics in dandruff pathology, advocating for microbiome-targeted therapies.